Establishing the Legal Framework for Family Group Conference to Resolve School Bullying in Malaysia - Ab Aziz, Norjihan; Mohamad Amin, Noor Shuhadawati; Ab Hamid, Zuraini; Ibrahim, Sarah Shahimah (Dewan Bahasa dan Pustaka, 2020)
Bullying cases at primary and secondary schools in Malaysia are in raise. The Education (School Disciplines) Regulations 1959 allows the headmaster to suspend or expel the perpetrator of bullies. Nevertheless, it was reported that 4,159, 4,120, 2,906 and 3,011 school bullying case respectively from 2012 up to 2015. This indicates that the current punishment is inadequate to solve the issue of school bullying. Punishing the perpetrator may not improve the perpetrator behaviour if he does not learn from the mistake. Instead of punishing the perpetrator, he needs to be educated and learnt the lessons from his act and its consequence on the victim. New Zealand and the United Kingdom have implemented the family group conference to deal with school bullying. Hence, this research aims to examine the nature of school bullying in Malaysia, and how the Malaysian law governs the issue. It is also aim to analyse how the family group conference resolves the issue of school bullying as implemented in New Zealand and the United Kingdom. Since there is no law in Malaysia which regulates the family group conference, it is suggested that it shall be introduced to resolve school bullying. This research adopts qualitative research methodology which focuses on doctrine analysis. Therefore, it is expected to establish a legal framework for the family group conference in dealing with school bullying cases in Malaysia, so that the parties can simply resolve the case among them and reach a win-win solution without referring to the authority.